Inventarization of Zingiberaceae in The West Block Batang Toru Forest of North Tapanuli North Sumatra - Nursahara Pasaribu (Talenta Publisher, 2021)
Zingiberaceae is one of the dominating plant family in West Block, Batang Toru forest region. According to preliminary survey, the forest is inhabited by many species of Zingiberaceae while information on its species richness is still limited. The aim of the study was to collect the species of Zingiberaceae in West Block, Batang Toru forest region, conducted from July to September 2018. Inventarization was conducted using exploration method, by exploring along designated tracking ways. The study found 18 species of Zingiberaceae belonging to 10 genera was obtained, two of them were Alpinia hansenii and Boesenbergia belalongensis were new record in Sumatra. From all species that was found, two species were known to live as epiphytes and the other 16 were terresterials. Zingiberaceae occur in varying habitats, starting from forest edge, open area with optimum sunlight and inside forest floor. The most species found belong to Globba and Amomum.Batang Toru Forest